SYNTHESIS AND CHARACTERIZATION OF A CHITOSAN-BASED CITRIC ACID-CROSSLINKED ENCAPSULANT SYSTEM - Anne Bernadette s Agu; Precious Japheth L Benablo; Vince St D Mesias; David Jr P Penaloza (Journal of the Chilean Chemical Society, 2019)
An encapsulant system was prepared via crosslinking of chitosan using citric acid as a crosslinker. FTIR spectroscopy, particle size and zeta potential analyses confirmed successful crosslinking, appropriate particle size and colloidal stability. Encapsulation capability of the said material was investigated using fluorescence spectroscopy. The effect of pH on the crosslinked chitosan particles was also conducted.